Pengaruh Struktur Kepemilikan, Struktur Modal, Karakteristik terhadap Nilai Perusahaan dengan Manajemen Laba dan Arus Kas (International Forum of Researchers and Lecturers, 2025)
By using earnings management and cash flow as intervening variables, this study aims to investigate how company value is influenced by ownership structure, company characteristics, and capital structure. This research method employs a quantitative approach. The secondary data used in this study comes from the financial statements of mining sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. Smart-PLS software is used to perform data analysis. Out of the eleven proposed hypotheses, only hypothesis H3 is accepted, which indicates that Ownership Structure has a significant impact on Company Value.